SMALL CLAIM COURT : PRINCIPLE CONCRETIZATION IN LAWSUIT SETTLEMENT - Peni Rinda (UNISSULA, 2021)
The purpose of this research is to examine the provisions of civil procedural law in settling a lawsuit, to know the form of simple, fast, and low-cost concretization in simple lawsuit settlement. The research method uses the research object of simple, fast, and low-cost concretization in the settlement of a simple claim, normative juridical approach, the type of data used in this study is secondary data, which is sourced from the literature. Secondary data consists of primary legal materials, secondary legal materials, legal material collection techniques carried out by literature and the internet, while the data analysis method is analyzed descriptively qualitatively. The results show that the provisions of civil procedural law in resolving claims in court so far have been using the basis of HIR, which do not differentiate between complicated and simple case examinations so that the time for settlement is the same. The process starting from submitting/registering a lawsuit, determining the day of trial by the head of the panel of judges, the parties being summoned appropriately, the trial, evidence to the verdict took a long time, namely 6 months (SUPREME COURT CIRCULAR No. 6 of 1992), so the Supreme Court issued SUPREME COURT CIRCULAR No. 2 of 2014 which provides a time limit for completing the case of five (5) months. The simple, fast, and low-cost principles of concretizing a small claim court can be seen in the settlement stage. Settlement of a simple lawsuit is divided into 4 (four) stages, namely: 1), preliminary stage, 2) stage of case examination, 3). The objection request stage and 4), the simple action decision stage. This simple lawsuit settlement process should take a maximum of 25 (twenty-five) days. The simple principle is embodied in the shortened settlement process mechanism, the fast principle is realized within 25 days of completion, a peace that does not use the provisions of Supreme Court rules No.1 of 2016, while the principle of low cost is realized from a simple settlement mechanism, will be affected by the cost of the case.